Blockchain as an Instrument of Decentralized Social Order and Democratic Reconfiguration - Darmawan, Didit; da Silva, Basilio dos Santos; da costa, Salvador (Metromedia, 2025)
This study investigates the conceptual and operational impact of blockchain technology on efforts to build decentralized democratic structures. Through a literature-based analysis, it examines how blockchain reshapes governance models, economic interactions, and collective organization by embedding trust and decision-making into digital protocols. While proponents advocate for its transparency, disintermediation, and autonomy, the findings reveal that blockchain systems often reproduce new forms of exclusion and asymmetrical control. Key issues include the opacity of algorithmic authority, unequal access to digital infrastructure, and the ideological framing of decentralization as inherently democratic. The study explores the dual nature of blockchain as both a tool for participatory experimentation and a vehicle for technological governance that may obscure accountability. It emphasizes the need for critical reflection on how blockchain infrastructures are designed, governed, and interpreted within evolving political and economic contexts. By engaging with interdisciplinary perspectives from sociology, political theory, and information systems, the research contributes to deeper understanding of the normative tensions within decentralized technologies. It argues that the democratic potential of blockchain depends not on its technical features alone, but on the collective will to embed justice, inclusion, and transparency into its architecture.